2019
DOI: 10.1002/cssc.201900279
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Catalysis with Antagonistic Catalysts Compartmentalized in the Dispersed and Continuous Phases of a Pickering Emulsion

Abstract: Ta ndemcatalysis combines multiple conversion steps, catalysts, and reagents in one reaction medium, offering the potential to reduce waste and time. In this study,P ickeringe mulsionsemulsions stabilized by solidp articles-are used as easy-topreparea nd bioinspired, compartmentalized reaction media for tandemc atalysis. Making use of simple and inexpensive acid and base catalysts, the strategy of compartmentalization of two noncompatible catalysts in both phases of the emulsion is demonstrated by using the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Bruijnincx et al showed that the solid particles in PEs cannot only serve as stabilizing components but also aid in compartmentalizing antagonistic catalysts. 92 They formulated w/o PEs containing both homogeneous acid and base catalysts. The acid catalyst was confined within the aqueous phase while the organic acid was dissolved within the oil phase (Table 1, entry 5).…”
Section: Advances In Pacmentioning
confidence: 99%
“…Bruijnincx et al showed that the solid particles in PEs cannot only serve as stabilizing components but also aid in compartmentalizing antagonistic catalysts. 92 They formulated w/o PEs containing both homogeneous acid and base catalysts. The acid catalyst was confined within the aqueous phase while the organic acid was dissolved within the oil phase (Table 1, entry 5).…”
Section: Advances In Pacmentioning
confidence: 99%
“…Recently, such solid particle‐stabilized emulsions, so‐called Pickering emulsions (PEs) have been receiving increased attention for their application in biphasic catalysis [17–19] . The solid particles at the boundary layer in PEs serve to compartmentalize and to protect the dispersed phase from the continuous phase, for example, allowing multiple reactions to be mediated consecutively [20–22] . The catalysts can then be dissolved in both phases, or the solid emulsifier itself can be endowed with catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…This microreactor was used to demonstrate the advantage of Pickering stabilized droplets over non‐stabilized droplets for biphasic flow catalysis, using the acid–base catalyzed deacetalization–Knoevenagel condensation of benzaldehyde dimethyl acetal as probe reaction. We previously showed PEs to positively influence this reaction in batch [15] . In this microreactor, the progress of the acid‐catalyzed deacetalization reaction, could be followed with in situ Raman spectroscopy, at various temperatures with both stabilized and non‐stabilized droplets.…”
Section: Figurementioning
confidence: 99%
“…[9] Previous research has mainly focused on the formation and stabilityo fP Es [10][11][12] to replace surfactant-stabilizede mulsions for pharmaceutical and cosmetic applications. [13] More recently, the use of batch PEs as reaction media for catalysis [14][15][16] has drawnattention,a na pproach that comes with considerable potentialb ut also with experimental challenges. Batch PEs are preparedb yv igorous stirring and as ar esult show broad droplet size distributions, making it difficult to measure kinetics, for example.…”
mentioning
confidence: 99%
See 1 more Smart Citation